THE EFFECT OF CAREER DEVELOPMENT, JOB STABILITY, WORK ENVIRONMENT, AND COMPENSATION ON EMPLOYEE LOYALTY AT PT WARLBOR INTERNATIONAL INDONESIA - Difa Sobri; Habibuddin Nasution; Magneta Hisyam; Sriwati Sriwati; Eti Murni Halawa (RADJA PUBLIKA, 2026)
Employee loyalty is one of the key factors that determines a company’s long-term success. This study aims to analyze the effects of career development, job stability, work environment, and compensation on employee loyalty at PT Warlbor International Indonesia. The study employed a quantitative approach with a causal-associative design. Data were collected through closed-ended questionnaires completed by 135 company employees using a five-point Likert scale. The results of multiple linear regression indicate that all independent variables—career development, job stability, work environment, and compensation—have a positive and significant effect on employee loyalty. Career development contributed 0.35 units, job stability 0.25 units, work environment 0.30 units, and compensation 0.28 units to the improvement of employee loyalty. Overall, the findings suggest that companies that effectively manage these factors are better able to strengthen employee loyalty, which in turn can improve productivity and organizational performance. This study provides a theoretical contribution to the human resource management literature and offers practical recommendations for more strategic policy management in retaining high-quality employees.